2003
DOI: 10.1208/pt040342
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyols on the conformational stability and biological activity of a model protein lysozyme

Abstract: The purpose of this study was to investigate the stabilizing action of polyols against various protein degradation mechanisms (eg, aggregation, deamidation, oxidation), using a model protein lysozyme. Differential scanning calorimeter (DSC) was used to measure the thermodynamic parameters, mid point transition temperature and calorimetric enthalpy, in order to evaluate conformational stability. Enzyme activity assay was used to corroborate the DSC results. Mannitol, sucrose, lactose, glycerol, and propylene gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…DSC has been employed to assess protein structural stability by several researchers. 32,33 The thermal denaturation of a protein occurs at the thermal transition temperature (T m ) which is calculated as the midpoint of the thermogram peak, and integration of the area under the peak gives the calorimetric enthalpy (ΔH). Figure 1 shows the melting of lysozyme under several buffer conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DSC has been employed to assess protein structural stability by several researchers. 32,33 The thermal denaturation of a protein occurs at the thermal transition temperature (T m ) which is calculated as the midpoint of the thermogram peak, and integration of the area under the peak gives the calorimetric enthalpy (ΔH). Figure 1 shows the melting of lysozyme under several buffer conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This is consistent with the literature value of 73.7 ± 0.6°C and 59 ± 5 kcal·mol −1 ·°C −1 measured for lysozyme in 4.85% (w/v) NaCl. 32 One hypothesis for the mechanism of structural stabilization of lysozyme in the presence of sugars is the concept of preferential hydration of protein. 13,30 The preferential hydration mechanism proposes that sugars are excluded from the environment around the protein and are replaced by water.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the evaluation of the influence of polyols on lysozyme by Singh and Singh (46), thermodynamic mDSC measurements and biological activity analysis correspond to each other because it was shown that polyols are capable of providing protection against various degradation mechanisms causing protein conformational destabilization associated with a decline in biological activity. Additionally, mDSC predictions of the stability of interleukin-1 receptor type I (IL-1R) in the presence of various preservatives could be verified by means of SE-HPLC data (55).…”
Section: Discussionmentioning
confidence: 98%
“…Also changes of the protein hydration properties in the presence of excipients have been considered with regard to stability [34][35][36].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%